Antiviral Activity of Fecal Water Samples from HIV-1 Infected Subjects Treated with a Specific Probiotic Formulation - Falasca, Francesca; Cavallari, Eugenio Nelson; Innocenti, Giuseppe Pietro; Scagnolari, Carolina; Mezzaroma, Ivano; Santinelli, Letizia; Ceccarelli, Giancarlo; Vullo, Vincenzo; Turriziani, Ombretta; d'Ettorre, Gabriella (Current HIV research, 2019)
The aim of the study was to investigate if the supplementation with multistrain probiotics may be able to modulate T cell response in HIV-1 infected patients and to evaluate the anti-HIV activity of probiotic by studying fecal water (FW) samples. Three HIV-1-positive patients (Pt1, Pt2 and Pt3) on long-term suppressive combined antiretroviral therapy (cART) received a specific multi-strain probiotic supplementation (Vivomixx ®), for six months (T6). Levels of T cell subsets were evaluated by flow cytometry. Anti- HIV activity of FW samples was evaluated in vitro. CD4+ T cells levels increased in all HIV-1 infected patients whereas activation markers (CD38 and HLA-DR) were decreased both on CD4+ and CD8+ T cells. FW samples presented an increased inhibitory activity against HIV-1 compared to T0 (FW-Pt1: T0 =40%, T6 = 65% of reduction; FW Pt2: T0 = 26%, T6 = 46% of reduction; FW Pt3: T0 = 47%, T6 = 94% of reduction). Our data suggest that the administration of the specific probiotic formulation improves the antiviral status of people living with HIV-1 under cART, also modulating T cell response. Anti-HIV activity of FW may have several public health and social implications for sexually transmitted diseases that need to be further explored.